Efeito da niacina e da monensina sódica no desempenho de novilhos em confinamento - Magliocca, F. D.; Silveira, Antonio Carlos [UNESP]; Furlan, L. R.; Arrigoni, M. D.; Costa, Ciniro [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
The objective of this study was to evaluate the effects of supplementation of combined and single monensin and niacin on the productive performance of crossbred young bulls (european/zebu) aged 11 months and initial average liveweight of 248 kg. The experimental design was a factorial randomized arrangement. The treatments were: T1-check, T2-niacin, T3-monensin and T4-niacin+monensin. All the treatments were isoproteic (11 %CP) and isoenergetic (78% TDN), composed of 57.3% roughage and 42.7% concentrate (soybean meal, maize, minerals and buffer). Data was collected over a period of 85 days, with liveweight measured every 28 days. It was conclued that, for this diet, the single supplementation of niacin does not increase the performance of bulls, and therefor it is not recommended. However, the ionophore monensin, single or on in combination with niacin, improves the performance of the animals up to 56 days of feedlot.

O trabalho teve por objetivo avaliar o efeito conjunto e isolado dos aditivos monensina e niacina, no desempenho produtivo de novilhos cruzados (taurino x zebuíno), com idade média de onze meses e peso médio de 248 kg, terminados em regime de confinamento. O delineamento experimental foi aleatorizado, com os seguintes tratamentos: T1-testemunha, T2-niacina, T3-monensina e T4-niacina+monensina. As rações foram isoprotéicas (11% PB) e isoenergéticas (78%) NDT), constituídas por 57,3% de volumoso (silagem de milho) e 42,7% de concentrado (farelo de soja, milho,minerais e tamponante) em todos os tratamentos. O período de coleta de dados foi de 85 dias, com pesagens a cada 28 dias. Concluiu-se que, para essa dieta, não se recomenda o emprego isolado da niacina na terminação de novilhos, sendo que o ionóforo monensina, isoladamente ou em combinação com a niacina, melhora o desempenho dos animais até 56 dias de confinamento.
The effect of niacin and monensin on the performance of young bulls at feedlot
Keywords: CONFINEMENT; BOVINES; ADDITIVES; ISOPROTEIC TREATMENTS; ISOENERGETIC TREATMENTS; INDUSTRIAL CROSSBRED